Adsorption of sodium dodecyl sulfate onto precipitate in treatment of vat dark blue BO by dissolved air flotation. Issue 15 (3rd August 2018) - Xia, Hongyun; Zhao, Xuyun; Zhao, Xiang; Yao, Ping; Zhang, Haoyu
ABSTRACT: Vat dark blue BO-simulated wastewater was treated by dissolved air flotation (DAF). In this process, the interactions of sodium dodecyl sulfate (SDS) and resulting DAF process precipitates were investigated by infrared spectroscopy and kinetic methods. Fourier transform infrared analysis revealed that γ values (cm −1 ) for asymmetric and symmetric stretching vibrations of CH2 groups for SDS-treated precipitation shifted toward higher in comparison to pure SDS, showing strong SDS and precipitate interactions. This showed the chemical adsorption of SDS onto precipitate surfaces. Adsorption data were well described by a pseudo-second-order model, with an adsorption activation energy of 42.602 kJ mol −1, further predicting an SDS chemisorption uptake process by the precipitate. SDS could be considered as one of the most efﬁcient flotation agents for the removal of vat dark blue BO in DAF processing.